Video streaming based on temporal frame transcoding - Fadlallah, Fadlallah Ali; Khalifa, Othman Omran; Hassan Abdalla Hashim, Aisha (American Scientific Publishers, 2016)
In the last few years, different types of interactive multimedia services were introduced such as distance learning, video conferencing, video telephony and many others, which are used as one of the best means of communication in a daily life. However, the most challenging task is to deliver these services in a different quality for user’s demands out of these services is video Streaming. This paper is proposed a new video streaming technique to reduce the amount of video frames that you need to send across networks. It is employing smart frame skipping module (SFSM) to skip a certain frame of video in the server and sent the adapted video stream while receiving video the client will re-construct the frame which were dropped from video in the server. The evaluation of the proposed scheme is conducted. Various parameters were used with different samples videos.